Dramatic band gap reduction incurred by dopant coordination rearrangement in Co-doped nanocrystals of CeO2 - T. S. Wu (Nature Portfolio, 2017)
Abstract A dramatic band gap narrowing of 1.61 eV has been observed in Co-doped nanocrystals of CeO2 (ceria), as a result of thermal annealing, without changing the ceria crystal structure and the Co concentration. As demonstrated by x-ray absorption fine structures, thermal annealing incurs an oxygen coordination rearrangement around Co atoms from an octahedral coordination to a square-planar coordination. First principle calculation using density functional theory reveals two stable oxygen coordination types surrounding Co, consistent with the experimental observation. The band gap values calculated for the two stable coordination types differ dramatically, reproducing the experimentally observed band gap narrowing. These prominent effects due to local structure rearrangement around dopant atoms can lead to unprecedented methods for band gap engineering in doped nanocrystal oxides.